2004
DOI: 10.1111/j.1464-410x.2004.05170.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of the bladder exstrophy‐epispadias complex: analysis of 232 families

Abstract: OBJECTIVETo identify genetic and nongenetic factors contributing to the risk of bladder exstrophyepispadias complex (BEEC). PATIENTS AND METHODSIn all, 285 families with BEEC were invited to participate in the study, and 232 of them were recruited. Epidemiological information was obtained from 151 of the consenting families, with a detailed clinical genetic examination of 94 probands. In all, 440 DNA samples were collected from 163 families for molecular analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 32 publications
2
95
1
1
Order By: Relevance
“…Contrary to previous findings describing an overrepresentation of very young mothers of BEEC children 2 but consistent with Boyadjiev et al, 6 we only found two mothers younger than 20 years. Furthermore, we detected no differences in parental age among the different phenotypes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Contrary to previous findings describing an overrepresentation of very young mothers of BEEC children 2 but consistent with Boyadjiev et al, 6 we only found two mothers younger than 20 years. Furthermore, we detected no differences in parental age among the different phenotypes.…”
Section: Discussionsupporting
confidence: 88%
“…Due to its low prevalence, epidemiological data on non-genetic risk factors are limited. 6 The present survey represents one of the largest to be conducted among BEEC families to date.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that genetic factors contribute to the development of these malformations; in particular, CNV studies in sporadic patients have identified de novo events that occur in specific chromosomal regions (Bartels et al, 2011;Boocock & Donnai, 1987;Boyadjiev et al, 2004;Cuschieri & EUROCAT Working Group, 2001;Draaken et al, 2010;Falcone et al, 2007;Keppler-Noreuil, 2001;Ludwig et al, 2009;Marcelis et al, 2011;Schramm et al, 2011aSchramm et al, , 2011bShapiro et al, 1984). We hypothesized that CNVs affecting coding regions that occur after twinning might contribute to discordance in MZ twin pairs with ARM or the BEEC.…”
mentioning
confidence: 99%
“…Prevalence at birth ranges from 1/30,000 for CBE to 1/200,000 for CE (4). There is a greater proportion of affected males than females, ranging from 1.8:1 to 6:1 (5,6). While the etiology of BEEC remains unknown, strong evidence exists linking its development to genetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the patients with BEEC do not have developmental delays, and with the exception of CE, there are few anomalies outside of the urogenital system (5,6). The associated anomalies observed in BEEC are mesodermderived, including omphalocele, hernias, kidney agenesis, imperforate anus, and pelvic dysplasia.…”
Section: Introductionmentioning
confidence: 99%